2017
DOI: 10.1186/s12864-017-3905-1
|View full text |Cite
|
Sign up to set email alerts
|

Novel Plasmodium falciparum metabolic network reconstruction identifies shifts associated with clinical antimalarial resistance

Abstract: BackgroundMalaria remains a major public health burden and resistance has emerged to every antimalarial on the market, including the frontline drug, artemisinin. Our limited understanding of Plasmodium biology hinders the elucidation of resistance mechanisms. In this regard, systems biology approaches can facilitate the integration of existing experimental knowledge and further understanding of these mechanisms.ResultsHere, we developed a novel genome-scale metabolic network reconstruction, iPfal17, of the ase… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 157 publications
1
38
0
Order By: Relevance
“…Genetic investigations on the role of TCA cycle enzymes in P. falciparum have revealed non-essentiality of all genes of the cycle except FH and malate-quinone oxidoreductase to asexual intra-erythrocytic stages (23). Recently, a metabolic network reconstruction of pathways in artemisinin resistant P. falciparum strains has identified FH reaction as uniquely essential to these parasites (24). Biochemical characterization of PfFH could throw light on unique features of the enzyme and also provide leads for the development of inhibitors.…”
mentioning
confidence: 99%
“…Genetic investigations on the role of TCA cycle enzymes in P. falciparum have revealed non-essentiality of all genes of the cycle except FH and malate-quinone oxidoreductase to asexual intra-erythrocytic stages (23). Recently, a metabolic network reconstruction of pathways in artemisinin resistant P. falciparum strains has identified FH reaction as uniquely essential to these parasites (24). Biochemical characterization of PfFH could throw light on unique features of the enzyme and also provide leads for the development of inhibitors.…”
mentioning
confidence: 99%
“…Under standard growth conditions, i AM-Pf480 correctly predicted 95% and 71% for the single gene knockouts and drug inhibition phenotypes, respectively ( Fig 2B , Table B and C in S1 Tables ). We also compared i AM-Pf480 gene essentiality predictions to i TH366[ 17 ], i Pfa[ 18 ] and i Pfal17[ 19 ], using our set of experimentally validated targets (Table B and C in S1 Tables ), which revealed that i AM-PF480 accounts for a larger scope of genomic content, a larger biochemical complement, and functionally outperformed previously published P . falciparum models (see supplementary material, Fig A and Table L in S1 Text , Table B and C in S1 Tables ).…”
Section: Resultsmentioning
confidence: 97%
“…This medium also contains high levels of other metabolites such as glutathione, hypoxanthine, glutamine, and many amino acids, which are correlated with phenol red and/or HEPES abundances. Third, we measured metabolites not expected to be produced or consumed by Plasmodium ( 2 ). For example, kynurenine is present in erythrocytes, derived from the amino acid l -tryptophan ( 29 , 30 ), and is not known to be involved in P. falciparum metabolism ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Omics approaches, such as genomics, transcriptomics, and proteomics, are widely used, but the limited annotation of the parasite’s genome makes these data sets challenging to interpret. One way to alleviate this lack of functional knowledge is to use network-based modeling to contextualize noisy or sparse data and facilitate the interpretation of complex data ( 2 ). Additionally, the measurement of direct mediators of the phenotype, such as signaling and biosynthetic metabolites, can improve the ability to characterize phenotypes mediated by proteins that are not yet annotated in the genome.…”
Section: Introductionmentioning
confidence: 99%